The Deubiquitinating Enzyme Cylindromatosis Dampens CD8+ T Cell Responses and Is a Critical Factor for Experimental Cerebral Malaria and Blood–Brain Barrier Damage - Schmid, Ursula; Stenzel, Werner; Koschel, Josephin; Raptaki, Maria; Wang, Xu; Naumann, Michael; Matuschewski, Kai; Schlüter, Dirk; Nishanth, Gopala (Frontiers in Immunology, 2017)
Cerebral malaria is a severe complication of human malaria and may lead to death of Plasmodium falciparum infected individuals. Cerebral malaria is associated with sequestration of parasitized red blood cells within the cerebral microvasculature resulting in damage of the blood brain barrier and brain pathology. Although CD8+ T cells have been implicated in the development of murine experimental cerebral malaria (ECM), several other studies have shown that CD8+ T cells confer protection against blood-stage infections. Since the role of host deubiquitinating enzymes (DUBs) in malaria is yet unknown, we investigated how the DUB CYLD, an important inhibitor of several cellular signalling pathways influences the outcome of ECM. Upon infection with Plasmodium berghei ANKA (PbA) sporozoites or (PbA)-infected red blood cells, at least 90% of Cyld-/- mice survived the infection, whereas all congenic C57BL/6 mice displayed signatures of ECM, impaired parasite control, and disruption of the blood brain barrier integrity. Cyld deficiency prevented brain pathology, including hemorrhagic lesions, enhanced activation of astrocytes and microglia, infiltration of CD8+ T cells and apoptosis of endothelial cells. Furthermore, PbA-specific CD8+ T cell responses were augmented in the blood of Cyld-/- mice with increased production of interferon-γ and granzyme B and elevated activation of Protein kinase C-θ and NF-κB. Importantly, accumulation of CD8+ T cells in the brain of Cyld-/- mice was significantly reduced compared to C57BL/6 mice. Bone marrow chimera experiments showed that the absence of ECM signatures in infected Cyld-/- mice could be attributed to hematopoietic and radioresistant parenchymal cells, most likely endothelial cells that did not undergo apoptosis. Together, we newly identify that host deubiqutinating enzymes play an important role in ECM and that CYLD promotes ECM promoting it as a potential therapeutic target for adjunct therapy to prevent cerebral complications of severe malaria.